Effect of high-intensity intermittent rehabilitation training on physical function, gut microbiome and metabolite after percutaneous coronary intervention in patients with coronary heart disease - Lei Jiang; Pu Liu; Mei Wang; Qiufeng Deng; Jiangpeng Wang; Yan Jiang; Ye Zhu; Haoyu Meng; Xiao Lu; Xiangqing Kong; Leilei Chen (Frontiers in Cardiovascular Medicine)
BackgroundPostoperative rehabilitation exercise training after percutaneous coronary intervention (PCI) is crucial for coronary heart disease (CHD) patients in restoring health and preventing recurrence, including high-intensity interval training (HIIT). However, the impact of HIIT on cardiopulmonary function, gut microbiome and metabolite remains underexplored.MethodsThis study included 60 patients with CHD who underwent percutaneous coronary intervention (PCI). Participants were divided into two groups: 33 in the moderate-intensity continuous training (MCT) group and 27 in the high-intensity interval training (HIIT) group. We assessed difference between two training in cardiopulmonary function, 6-minute walk test (6MWT) performance, biochemical indicators, plasma metabolites, and gut microbiome feature at baseline and after 3 months training. Furthermore, we analyzed 6MWT association to gut microbiome and metabolites with group differences.ResultsThe 6MWT showed significantly greater improvement in the HIIT group compared to the MCT group (P = 0.0024). Both groups showed reductions in low-density lipoprotein (LDL) levels and increases in peak oxygen uptake (VO2 peak) after training, but the HIIT group demonstrated a larger effect size in these measures. Moreover, subgroup analysis revealed that patients with a history of myocardial infarction (MI) in the HIIT group experienced a more substantial increase in VO2 peak compared to the MCT group (P = 0.04). In addition, we identified 29 gut microbial species and 30 plasma metabolites that were differentially enriched between the two groups, with some showing a significant impact on 6MWT performance.ConclusionsHigh-intensity interval training significantly improves 6MWT performance and exercise tolerance in cardiac rehabilitation patients, particularly enhancing VO2 peak in those with a history of MI. HIIT also appears to modulate the gut microbiome, increasing the abundance of Clostridiales and decreasing traumatic acid content, which may contribute to the observed improvements in exercise tolerance.